Thailand Diabetes Registry Project: Type of diabetes, glycemic control and prevalence of microvascular complications in children and adolescents with diabetes - Supawadee Likitmaskul (2018)
Objective: To determine the etiology, glycemic control and prevalence of microvascular complications in Thai diabetic patients who were diagnosed at the age of less than 18 years and who attended diabetes clinics in university or tertiary care hospitals. Material and Method: A cross-sectional, multi-center, hospital-based diabetes registry was carried out from diabetes clinics of 11 tertiary centers. Demographic data including laboratory results and microvascular complications were recorded. Results: Two-hundred-and-fifty out of the 9419 (2.66%) diabetic patients were diagnosed before the age of 18 years, 78% had Type1 diabetes (T1DM), 18.4% had Type2 diabetes (T2DM) and 3.6% had other types of diabetes. Mean HbA 1C of T1DM was 9.3 ± 2.5, T2DM was 9.7 ± 2.6 and other types of diabetes were 8.6 ± 4%. The majority of patients had poor glycemic control according to ADA and WHO guidelines. The percentage of patients who had diabetes for more than 5 years but had not been screened for nephropathy and retinopathy were 57.7% and 16% in T1DM and were 46.4% and 14.2% in T2DM respectively. A significant correlation between microvacular complications (nephropathy and retinopathy) and duration of disease was found in T1DM (p <0.001). Conclusion: The majority of Thai children and adolescents with diabetes had T1DM and unsatisfactory glycemic control. Screening for microvascular complications was under international standard. The national strategic plan for management of this disease especially in this age group should be urgently implemented.